Heart rate variability in elite triathletes, is variation in variability the key to effective training? A case comparison - Plews, D. J.; Laursen, P. B.; Kilding, A. E.; Buchheit, M. (European Journal of Applied Physiology, 2012)
Measures of an athlete`s heart rate variability (HRV) have shown potential to be of use in the prescription of training. However, little data exists on elite athletes who are regularly exposed to high training loads. This case study monitored daily HRV in two elite triathletes (one male: 22 year, VO2max 72.5 ml/kgmin; one female: 20 year, VO2max 68.2 ml kg min-1) training 23 ± 2 h per week, over a 77-day period. During this period, one athlete performed poorly in a key triathlon event, was diagnosed as non-functionally over-reached (NFOR) and subsequently reactivated the dormant virus herpes zoster (shingles). The 7-day rolling average of the log-transformed square root of the mean sum of the squared differences between R-R intervals (Ln rMSSD), declined towards the day of triathlon event (slope = -0.17 ms/week; r 2 = -0.88) in the NFOR athlete, remaining stable in the control (slope = 0.01 ms/week; r 2 = 0.12). Furthermore, in the NFOR athlete, coefficient of variation of HRV (CV of Ln rMSSD 7-day rolling average) revealed large linear reductions towards NFOR (i.e., linear regression of HRV variables versus day number towards NFOR: -0.65%/week and r 2 = -0.48), while these variables remained stable for the control athlete (slope = 0.04%/week). These data suggest that trends in both absolute HRV values and day-to-day variations may be useful measurements indicative of the progression towards mal-adaptation or non-functional over-reaching.This study examined the effects of pre-cooling duration on performance and neuromuscular function for self-paced intermittent-sprint shuttle running in the heat. Eight male, team-sport athletes completed two 35-min bouts of intermittent-sprint shuttle running separated by a 15-min recovery on three separate occasions (33°C, 34% relative humidity). Mixed-method pre-cooling was completed for 20 min (COOL20), 10-min (COOL10) or no cooling (CONT) and reapplied for 5-min mid-exercise. Performance was assessed via sprint times, percentage decline and shuttle-running distance covered. Maximal voluntary contractions (MVC), voluntary activation (VA) and evoked twitch properties were recorded pre- and post-intervention and mid- and post-exercise. Core temperature (T c), skin temperature, heart rate, capillary blood metabolites, sweat losses, perceptual exertion and thermal stress were monitored throughout. Venous blood draws pre- and post-exercise were analyzed for muscle damage and inflammation markers. Shuttle-running distances covered were increased 5.2 ± 3.3% following COOL20 (P < 0.05), with no differences observed between COOL10 and CONT (P > 0.05). COOL20 aided in the maintenance of mid- and post-exercise MVC (P < 0.05; d > 0.80), despite no conditional differences in VA (P > 0.05). Pre-exercise T c was reduced by 0.15 ± 0.13°C with COOL20 (P < 0.05; d > 1.10), and remained lower throughout both COOL20 and COOL10 compared to CONT (P < 0.05; d > 0.80). Pre-cooling reduced sweat losses by 0.4 ± 0.3 kg (P < 0.02; d > 1.15), with COOL20 0.2 ± 0.4 kg less than COOL10 (P = 0.19; d = 1.01). Increased pre-cooling duration lowered physiological demands during exercise heat stress and facilitated the maintenance of self-paced intermittent-sprint performance in the heat. Importantly, the dose-response interaction of pre-cooling and sustained neuromuscular responses may explain the improved exercise performance in hot conditions.